PERSPEKTIF EKONOMI DAN BISNIS ISLAM MENGENAI PENGARUH INVESTASI DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT PENGANGGURAN TERBUKA DI PROVINSI JAWA TIMUR TAHUN 2002-2021 - Kartono, keris; Efendi, Ramdan; Hidayat, Rahmat; Putri, Wulan Purnama; Khaitami, Siraddjudin (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
The purpose of this study is to prove whether the effect of investment and the human development index (HDI) on the open unemployment rate in East Java Province in 2002-2021. Data collection uses secondary data from Investment, Open Unemployment Rate, Minimum Wage, and HDI in East Java Province obtained from the Badan Pusat Statistik, in the form of time series data from 2002 to 2021. The method of analysis in this study uses the multiple regression analysis method. which consists of more than one independent variable which is processed using the SPSS 26 application obtained TPT Regression Equation = 2.662 - 0.121 Invest - 0.168 HDI. The results of this study show that variable investment (INVEST) has a large negative impact on the unemployment rate. On the other hand, the Human Development Index (HDI) variable has a negative impact on the unemployment rate and is insignificant.